2012
DOI: 10.1021/ja210856v
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Cooperative Protein Structural Dynamics of Homodimeric Hemoglobin from 100 ps to 10 ms with Pump–Probe X-ray Solution Scattering

Abstract: Proteins serve as molecular machines in performing their biological functions, but the detailed structural transitions are difficult to observe in their native aqueous environments in real time. For example, despite extensive studies, the solution-phase structures of the intermediates along the allosteric pathways for the transitions between the relaxed (R) and tense (T) forms have been elusive. In this work, we employed picosecond X-ray solution scattering and novel structural analysis to track the details of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 64 publications
7
137
0
Order By: Relevance
“…86, [332][333][334][335][336] Later, the same groups embarked in the study of dimeric hemoproteins, 337,338 with the aim to investigate cooperativity. Solution ps XRS is ideal when looking at conformational changes, large amplitude side chain motions and folding-unfolding processes and the above studies revealed several hitherto unknown details of the large scale protein dynamics.…”
Section: Picosecond Studiesmentioning
confidence: 99%
“…86, [332][333][334][335][336] Later, the same groups embarked in the study of dimeric hemoproteins, 337,338 with the aim to investigate cooperativity. Solution ps XRS is ideal when looking at conformational changes, large amplitude side chain motions and folding-unfolding processes and the above studies revealed several hitherto unknown details of the large scale protein dynamics.…”
Section: Picosecond Studiesmentioning
confidence: 99%
“…TRXSS is an effective method for probing photoinduced structural changes of molecules in solution and has been used to reveal the dynamics and mechanism of various molecular reaction systems ranging from small molecules [14][15][16][17] to biological macromolecules 18,19 . Although subpicosecond time resolution has been achieved in the case of X-ray 20-23 and electron [24][25][26] diffraction of solid samples and in X-ray absorption spectroscopy 27 of liquid samples, the temporal resolution of TRXSS based on synchrotron radiation 13 has been limited to only 100 ps, thus preventing the observation of ultrafast processes on the timescales of femtoseconds to picoseconds.…”
mentioning
confidence: 99%
“…1 This method was successfully applied to observe the structural dynamics of chemical reactions of small molecules in solution. [2][3][4][5][6][7][8] More recently, TR-WAXS was applied to track the conformational transitions of photo-active globular proteins [9][10][11][12][13][14][15][16] and proton pumps. [17][18][19][20] The structural interpretation of such TR-WAXS signals is challenging since, due to the orientational average inherent to solution X-ray scattering, WAXS patterns contain typically only 10-20 independent data points, 21 whereas proteins contain many more degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,15 Using such models, scattering curves for structural intermediates and low-resolution realspace electron densities of intermediates could be derived. 15 For a structural interpretation at the atomic level, TR-WAXS patterns have been calculated from structures determined by crystallography 9,10,14,16 or nuclear magnetic resonance (NMR). 13 In addition, Monte Carlo 14 and Molecular Dynamics (MD) simulations 4,5,10,16 have been used to refine structures a) jhub@gwdg.de; URL: http://cmb.bio.uni-goettingen.de/ against WAXS data.…”
Section: Introductionmentioning
confidence: 99%